2015
DOI: 10.1016/j.ajhg.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A Specific IFIH1 Gain-of-Function Mutation Causes Singleton-Merten Syndrome

Abstract: Singleton-Merten syndrome (SMS) is an infrequently described autosomal-dominant disorder characterized by early and extreme aortic and valvular calcification, dental anomalies (early-onset periodontitis and root resorption), osteopenia, and acro-osteolysis. To determine the molecular etiology of this disease, we performed whole-exome sequencing and targeted Sanger sequencing. We identified a common missense mutation, c.2465G>A (p.Arg822Gln), in interferon induced with helicase C domain 1 (IFIH1, encoding melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
161
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 24 publications
8
161
0
2
Order By: Relevance
“…In addition, patients may suffer from psoriasis, early-onset glaucoma and recurrent infections. Singleton-Merton syndrome is inherited in an autosomal dominant manner and caused by heterozygous mutations in IFIH1 (SGMRT1; OMIM 182250) or RIGI (SGMRT2; OMIM 616298) encoding cytosolic pattern recognition receptors for dsRNA [74,75]. Functional studies have shown that IFIH1 or RIGI mutations in patients act as gain-offunction mutations which results in constitutive type IFN activation.…”
Section: Singleton-merten Syndromementioning
confidence: 98%
“…In addition, patients may suffer from psoriasis, early-onset glaucoma and recurrent infections. Singleton-Merton syndrome is inherited in an autosomal dominant manner and caused by heterozygous mutations in IFIH1 (SGMRT1; OMIM 182250) or RIGI (SGMRT2; OMIM 616298) encoding cytosolic pattern recognition receptors for dsRNA [74,75]. Functional studies have shown that IFIH1 or RIGI mutations in patients act as gain-offunction mutations which results in constitutive type IFN activation.…”
Section: Singleton-merten Syndromementioning
confidence: 98%
“…Following the identification of IFIH1 mutations in various neuroimmunological disease states 9 , it was reported that a specific IFIH1 gain-of-function mutation can cause Singleton-Merten syndrome (SMS), an auto somal dominant disorder variably characterized by dental anomalies (early-onset periodontitis and root resorption), aortic and valvular calcification, glaucoma, psoriasis, contractures and acro-osteolysis 81 . Simultaneously, two distinct mutations in DDX58 (which encodes the cytosolic sensor of 5ʹ-triphosphate and 5ʹ-diphosphate RNA, RIG-I 82 ) were described that cause what the authors refer to as atypical SMS -in which glaucoma, aortic calcification and skeletal abnormalities are present in the absence of obvious dental problems 83 .…”
Section: Other Type I Interferonopathiesmentioning
confidence: 99%
“…Calcification per se may also enhance inflammation when present in the form of hyperphosphatemia-induced nanocrystals or calcium phosphate crystals [40,71]. It was recently shown that the Singleton-Merten syndrome, which includes both vascular and valvular calcification, might be due to mutations resulting in increased interferon activity [72], thereby supporting the concept that inflammation leads to calcification. It is interesting to note that infection, such as tuberculosis, commonly leads to calcified lesions, a process likely driven by inflammation.…”
Section: Signaling Pathways and Relation Of Calcific Diseasementioning
confidence: 99%